The Influence of Celebrity Endorsement, Brand Image and Brand Trust on Samsung Galaxy Smartphone Purchase Decision - Anggalia Wibasuri; Yuliani Oskar; Desta Saputri (Prosiding International conference on Information Technology and Business (ICITB), 2022)
Smartphone is a communication tool that can store messages and is very practical to use as a communication tool because it can be carried anywhere. The competition in the smartphone industry in Indonesia is getting tighter in achieving the top position or called the market leader. Samsung galaxy briefly topped the rankings in 2018. Samsung's trend in the Galaxy had experienced a decline in the following years. This researcher wants to examine consumers who have different reasons for making smartphone purchase decisions. This study aims to find out how much influence celebrity endorsement, brand image and brand trust have on Samsung galaxy purchasing decisions. The number of samples taken was 140 respondents with purposive sampling. Data analysis in this study used the Structural Equation Model (SEM). The results of this study show that Celebrity Endorstment, brand image, and brand trust influence the purchasing decision of Samsung Galaxy smartphones.Keywords—celebrity endorsement, brand image, brand trust, purchasing decision